Design and manufacture of dental-supported surgical guide for genioplasty - Li-dong Wang; Wen Ma; Shuai Fu; Chang-bin Zhang; Qing-ying Cui; Can-bang Peng; Ming Li (Elsevier, 2021)
Background/purpose: Genioplasty were used widely to correct chin deformities. The purpose of this study was to design and manufacture a dental-supported surgical guide for genioplasty surgery and assess for surgical accuracy. Materials and methods: eleven patients with chin deformities were treated in this study. The computed tomography (CT) data of the patient's skull and the digital dental models of stone dental models were acquired preoperatively. For each patient, a virtual three-dimensional (3D) model of the skull was constructed and enhanced with digital dental models. A surgical simulation was then performed using computer-aided surgical simulation (CASS) technology based on clinical examination and 3D cephalometry. The surgery was simulated preoperatively which allowed the design of a cutting guide and a dental-supported repositioning guide for genioplasty, which was then 3D-printed and used during operation after disinfection. After surgery, the outcome was evaluated by superimposing the postoperative CT model onto the preoperative model, recording the linear and angular deviation of landmarks and plane, then measuring the differences between the planned and actual outcomes. Results: The osteotomy and repositioning were successfully performed as planned using surgical guides. No inferior alveolar nerve damage was seen in this study. The dental-supported surgical guide showed excellent accuracy, with the largest differences between the planned and the postoperative chin segment being 0.9 mm and 3.2°. Conclusion: The dental-supported surgical guide designed preoperatively provided a reliable method of transfer genioplasty planning. This can assist surgeons in accurately performing osteotomy and repositioning bone segments during a genioplasty.